Emotional intelligence, psyhological contract violation and counterproductive work behaviour: Moderating effect of industrial relations cliamte / Raja Muhamad Yusof Raja Aziz - Raja Aziz, Raja Muhamad Yusof (Penerbit UiTM (UiTM Press), 2018)
Counterproductive work behaviour (CWB) continues to be a worldwide phenomenon and common problem in today's organizations and has been reported to have high rate of occurrences and serious negative impact either economically or socially. Hence, the primary objective of this research was to examine the direct relationship of two independent variables i.e. personal-related factor (Emotional Intelligence-EI) and organisational-related factor (Psychological Contract Violation- PCV) as the predictors of CWB. The moderating variable (Industrial Relations Climate-IRC) which was the focal point of the study had been included to examine the interaction effect on the relationship between the independent variables and the observed variables. From theoretical perspectives, three social theories had been identified to support the theoretical framework of the study namely social exchange theory, equity theory and social cognitive theory. A survey was administered to employees of the Malaysian National Automotive Manufacturing companies with a sample size of 373 cases. The focus group of the study involved employees of non-executives level, whom are covered under the collective agreement terms between the company and trade unions association. Non-probability sampling technique with proportional-quota method was adopted for this study. This research employed SPSS version 22.0 to analyse data and supported by PROCESS macro model 1 by Hayes A.F. (2013) for analysis on moderation assessment…